Gambaran Distribusi Frekuensi Faktor Risiko Kelainan Kongenital Pada Bayi Baru Lahir Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2009 Sampai Dengan Tahun 2018 - Ramadhan, Ahmad; Selomo, Makmur; Wahyudin, Bob (Bosowa Medical Journal, 2023)
Congenital abnormalities are also known as congenital defects or congenital disorders from birth. Congenital abnormalities are structural or functional changes that occur during the intrauterine period and can be identified before birth, at birth or detected later in life after the baby is born, such as hearing defects. The purpose of this study was to describe the distribution of risk factors for congenital abnormalities in newborns in several locations in Indonesia for the period 2009 to 2018. The research method used in this study was a Observasional descriptive method by describing the research results obtained from seven scientific research articles. The results of research from seven research journals obtained 207 research subjects at risk based on gestational age from a total of 492 research subjects, 288 research subjects at risk based on maternal age from a total of 640 research subjects, 74 research subjects at risk based on birth weight of a total of 220 research subjects, and 185 research subjects at risk based on gender from a total of 316 research subjects